Planning of truck platoons: A literature review and directions for future research. (January 2018) - Bhoopalam, Anirudh Kishore; Agatz, Niels; Zuidwijk, Rob
Highlights: We identify important planning issues in truck platooning. We provide a comprehensive classification of platooning operations. We critically review relevant operations research literature for platoon planning. We identify gaps in the literature and provide directions for future research. Abstract: A truck platoon is a set of virtually linked trucks that drive closely behind one another using automated driving technology. Benefits of truck platooning include cost savings, reduced emissions, and more efficient use of road capacity. To fully reap these benefits in the initial phases of technology deployment, careful planning of platoons based on trucks' itineraries and time schedules is required. This paper provides a framework to classify various new transportation planning problems that arise in truck platooning, surveys relevant operations research models for these problems in the literature and identifies directions for future research.